2019
DOI: 10.1038/s41598-019-56562-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous influence of sympathetic autonomic stress on Schlemm’s canal, intraocular pressure and ocular circulation

Abstract: This study aimed to investigate changes in Schlemm’s canal, intraocular pressure and ocular blood circulation following the activation of the sympathetic nervous system. Twenty healthy volunteers were enrolled in this study. The cold pressor test (CPT) was adopted. Cross-sectional area of Schlemm’s canal (SCAR), superficial and deep retinal vessel densities (s-RVD;d-RVD), pupil diameter (PD), intraocular pressure (IOP), mean ocular perfusion pressure (MOPP) and heart rate variability (HRV) were measured at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As of February 2022, over 3 billion doses of the COVID-19 vaccine have been administered, according to the report of National Health Commission of the People’s Republic of China [ 47 ]. Our study provides an early glance into the willingness and potential hesitancy to receive of a COVID-19 vaccine among students in grades 7–12 in urban China.…”
Section: Discussionmentioning
confidence: 99%
“…As of February 2022, over 3 billion doses of the COVID-19 vaccine have been administered, according to the report of National Health Commission of the People’s Republic of China [ 47 ]. Our study provides an early glance into the willingness and potential hesitancy to receive of a COVID-19 vaccine among students in grades 7–12 in urban China.…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 28 ] evaluated the level of IOP and the diameter of Schlemm’s canal following the cold pressor test (CPT), which activates the sympathetic nervous system. They verified that sympathetic activation leads to the dilation of Schlemm’s canal and a reduction in IOP.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 Nonetheless, this increase in blood pressure might not be perceived in healthy young subjects. [24][25][26] Additionally, Vianna et al 16 reported an enhancement in the gain of arterial baroreflex control of muscle sympathetic nerve activity in order to maintain the arterial blood pressure. That is reflected in our results with maintained MAP, in spite of the decrease in the HR.…”
Section: Discussionmentioning
confidence: 99%